The relationship between nasal fracture patients and weather conditions - Yeşim Yüksel; Cihan Bedel; Fatih Selvi; Okkes Zortuk; Mustafa Korkut; Yusuf Karanci (Journal of Preventive and Complementary Medicine)
Background: Isolated nasal bone fractures are among the most prevalent facial injuries. Although the relationship between weather conditions and nasal fractures has not been extensively studied, it is reasonable to hypothesize a correlation.Objectives: This study aimed to investigate the prevalence of isolated nasal bone fractures and explore potential correlations with weather conditions.Methods: We conducted a retrospective analysis of patients diagnosed with nasal fractures resulting from trauma between January and December 2023. Diagnosis was primarily based on physical examinations and direct radiography. Upon admission, we documented various climatic factors, including daily average air temperature, dew point, humidity, weather conditions (fair, cloudy, windy, or rainy), wind speed, atmospheric pressure, and precipitation.Results: Among the patients assessed, 103 were diagnosed with nasal fractures, yielding a prevalence rate of 0.027%. The mean age of the patients was 28.62 years, with females accounting for 31.1% of the cases. The peak frequency of nasal fracture incidents occurred in May and June. Statistical analysis revealed no significant difference in nasal fracture distribution across months (p=0.177). However, the incidence of nasal fractures varied by season, with the highest rates observed in autumn (27.7%), followed by spring and summer (both 25.3%).Conclusion: Our study indicates that the occurrence of nasal fractures tends to rise with higher temperatures, although seasonal distribution does not significantly impact its overall prevalence.